Uber Court: a look at recent sharing economy cases before the CJEU - Ferro, Miguel Sousa (2019)
This paper describes and discusses the two recent judgments of the CJEU regarding the clarification of the concept of information society services, both of which concern Uber. Although theses cases concern Uber, what is, a contrario, important to consider from the case-law is the broader context of the implication(s) of this case-law for EU law and the national regulation of the new sharing economy services – namely in what may affect the pending Airbnb case.